The Relationship Between E-Health Literacy Level and Health Anxiety in Individuals with Chronic Illnesses - Aysun Kazak Saltı; Evin Nehir Yazan (Ahi Evran Medical Journal, 2026)
Purpose: The aim of this study is to examine the relationship between e-Health literacy levels and health anxiety in individuals with chronic diseases.Materials and Methods: The sample of this cross-sectional study consisted of 117 individuals. Data were collected between September - November 2025 at a hospital in Mersin. The data were gathered using the “Individual Information Form (IIF)”, “e-Health Literacy Scale (e-HEALS)”, and the “Health Anxiety Scale (HAS)”. Descriptive statistics, independent samples t-test, one-way ANOVA (with Bonferroni post-hoc test), Pearson correlation analysis, and simple linear regression analysis were used for data analysis.Results: Among the participants, eHealth literacy was found to be negatively associated with age (p < 0.05) and positively associated with educational level (p < 0.01). No statistically significant differences were identified in terms of gender (p > 0.05). A considerable proportion of participants reported accessing health-related information through family members, social networks, and social media platforms. Moreover, no statistically significant relationship was found between e-Health literacy and health anxiety (p > 0.05).Conclusion: These findings highlight the importance of evaluating eHealth literacy and health anxiety together in the context of chronic disease. The observed patterns suggest the need for interventions that support access to reliable health information while taking psychosocial factors into account, thereby providing guidance for healthcare professionals.